PEMANFAATAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA - Anindyawati, Galuh Dwi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
In the junior high school level,  Indonesian language subjects, students consider text and literature-based learning to have a high level of saturation. Especially when in an environment students have low literacy. In reality, language and literature learning is a subject that requires concentration and astuteness in understanding the meaning of texts, both fiction and non-fiction. This research aims to analyze the influence of Wordwall learning media in improving Indonesian language learning outcomes for students in class VIII A of SMP Negeri 1 Slogohimo. The subjects of this research were 24 students in class VIII A of SMP Negeri 1 Slogohimo. The research method uses a quantitative and qualitative approach (mixed method). The type of research is classroom action research with research stages consisting of planning, implementing actions, observing and reflecting. Research instruments with tests, observations and questionnaires. Research data obtained from the pretest and posttest is in the form of a percentage of each respondent's total score and the average. The research results show that there is an increase in learning outcomes with the application of Wordwall media